Contextualized Education and Mother Tongue-Based Multilingual Instruction in Indonesian Indigenous Communities: A Systematic Literature Review - Selviana Haenkanes Turot; Asep Herry Hernawan; Budi Setiawan (Universitas Muhammadiyah Sumatera Utara, 2026)
Indonesia's multilingual complexity, comprising over 700 regional languages, contrasts sharply with the monolingual bias prevalent in formal primary education. While existing literature explores bilingual classroom dynamics, it often overlooks the systemic friction between national policy and localized implementation. This systematic literature review synthesizes 59 peer-reviewed studies to map how rural and indigenous schools negotiate this pedagogical environment. The findings reveal a structural bifurcation, where remote regions utilize mother tongues for cognitive survival, whereas western regions emphasize cultural preservation. Critically, the analysis identifies widespread organizational decoupling, wherein progressive decentralization policies are undermined by centralized, monolingual assessment metrics. To address this, the study introduces the Multi-Level Ecological-Contextual Model, an evidence-based conceptual blueprint designed to synchronize macro-policy, meso-community, and micro-classroom dimensions. While this framework requires subsequent empirical validation, it provides a novel systemic roadmap for institutionalizing linguistic equity. This review contributes a rigorous mapping of policy-practice decoupling, demonstrating that mother tongue instruction is a fundamental cognitive right rather than a cultural luxury, and establishes a foundation for restructuring primary education toward additive, resource-oriented multilingual frameworks.